State, Digital Surveillance, and Society – A Scoping Review - Andi Ainun Juniarsi Nur; Wahyu Gunawan; Yogi Suprayogi Sugandi (Dinasti Publisher, 2025)
The concept of state digital-surveillance has been recognized as a significant factor impacting individual privacy and social dynamics, drawing greater attention in sociological literature. However, existing studies often examine digital surveillance, social control, and privacy in isolation, and there is limited empirical research establishing clear causal links between state digital-surveillance and its broader societal impacts. As a result, there is a need for a confirmatory study that addresses this gap. The literature on the relationship between state digital-surveillance and its effects on privacy and autonomy remains fragmented, with few comprehensive studies exploring how surveillance practices shape societal structures. This scoping review utilizes the PCC model of PRISMA guidelines to investigate these connections. It focuses on the causal relationship between state digital-surveillance, individual freedoms, and societal control, providing an overview of existing literature and identifying areas for further research. Specifically, this review highlights the intersection of digital surveillance and social behavior, offering insights that map the complex linkages between state digital-surveillance and its effects on modern society.